An ultra-broadband, polarization and angle-insensitive metamaterial light absorber. (23rd December 2019) - Wu, Biao; Liu, Zhengqi; Liu, Guiqiang; Liu, Xiaoshan; Tang, Peng; Du, Guozhen; Yuan, Wen; Liu, Mulin
Abstract: We propose a new ultra-broadband metamaterial absorber based on a titanium–silica–titanium sandwich structure, which is composed of a periodic array of titanium–silica elliptical nanodisks and a titanium bottom film. The absorption bandwidth reaches 1376 nm in the wavelength range from the visible to near-infrared region with the spectral absorptivity  >90%. Moreover, the spectrally averaged absorption is up to 94.6%, indicating the achievement of ultra-broadband near-perfect absorption. In addition, the near-perfect absorption is polarization-independent and incident-angle insensitive. The ultra-broadband absorption mainly results from the strong plasmonic near-field coupling by the adjacent metal parts and the intrinsic material absorption in the wide wavelength range by the refractory metal. The proposed ultra-broadband metamaterial absorber could have broad application prospects in solar photovoltaic generation, infrared detection, and hot-electron devices.